2021
DOI: 10.5539/jas.v13n5p144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Starches as Gelling Agents for Micropropagation of Potato

Abstract: Unavailability of clean planting material is a major constraint of potato production in Eritrea. In vitro multiplication is proved to be a reliable solution; however, due to high media cost and initial investment, its use has been limited. The current study was carried out to evaluate the effectiveness of three starches (corn, potato and barley) of both laboratory and commercial grades as agar substitute, for micropropagation of potato. Single nodes of potato were sub-cultured into a fresh modified Murashige a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Similar results were obtained in a previous study conducted by Amlesom et al in 2021 [71], who evaluated the efficacy of three types of starch (corn, potato, and barley) in both laboratory and commercial grades as alternatives to agar for potato micropropagation.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were obtained in a previous study conducted by Amlesom et al in 2021 [71], who evaluated the efficacy of three types of starch (corn, potato, and barley) in both laboratory and commercial grades as alternatives to agar for potato micropropagation.…”
Section: Discussionsupporting
confidence: 88%
“…Cost reduction of up to 70% was achieved using enset starch as gelling agent without its effect on shoot multiplication and rooting. Similar results with 66 to 90% gelling agent cost reduction were reported using potato starch, rice flour, cassava flour and corn flour (Daud et al, 2011;Sharifi et al, 2010;Ogero et al, 2011;Amlesom et al, 2021) and balanga seeds (Jabeen et al, 2017). Therefore, use of low cost alternative media effectively reduced production cost for moringa micropropagation.…”
Section: Discussionsupporting
confidence: 73%
“…To mention some, commercial grade sugar in India for banana micro propagation (Ganapathi et al, 1995), solar illuminated tissue culture rooms in Cuba, refined and unrefined white and brown sugar for coconut culture (Bonaobra et al, 1994;Silvosa-Millado et al, 2020) and sugarcane in Ethiopia (Getnet et al, 2016). In addition, gelling agents such as isubgol, sago, enset starch, corn starch for the culture of fruit crops were reported (Bhattacharyya et al, 1994;Zimmerman et al, 1995;Mengesha et al, 2012;Amlesom et al, 2021;Dhawale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, starch is hydrolyzed by plant amylolytic enzymes during in vitro tissue culture (Lima et al, 2011). To evaluate this situation, Amlesom et al (2021) examined three alternative low-cost corn, potato, and barley starches at 50 g/L as a solidifying substitution for commercial agar for the micropropagation of potato. It has been found that substituting agar with alternative starches showed a significant reduction in the cost of a solidifying agent.…”
Section: Low-cost Options For Gelling Agentmentioning
confidence: 99%